Morfologia e desenvolvimento do sistema reprodutor em três espécies de Isoptera - Laranjo, Lara Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Kings of Isoptera supply large quantities of viable sperm to the queens. Nevertheless, the study of the male reproductive system of these insects has been neglected when compared to that of females. In order to fill this gap, this research aimed a comparative study of the reproductive system in different ages of termite males, including nymphs and winged reproductives. Thus, three species were chosen from three families that have different evolutionary positions: Cryptotermes brevis, Coptotermes gestroi and Silvestritermes euamignathus. Chapter I emphasized the production of sperm and development of seminal vesicles in last instar nymphs, alates and 6-month and 1-year-old kings of C. brevis. In nymphs, the sperm are restricted to the testicles. Chapter II focuses primarily on the histochemistry and ultrastructure of the seminal vesicles of C. gestroi and records the beginning of spermatogenesis in 3rd instar nymphs, even though 5th instar nymphs have not stored sperm in the seminal vesicles. In this species, individualized seminal vesicles have a secretory distal region and a proximal region with sperm storage function. In addition, the histochemistry showed polysaccharides and proteins present in the secretion of these structures at the distal region. In Chapter III, the evolution of the reproductive system in male of S. euamignathus was followed. The results showed an early maturation of the reproductive system of males and the increasing sperm production in kings of mature colonies. Additionally, morphological and histochemical data allowed us to infer that the seminal vesicles of kings function more likely as a sperm storage organ than secretory structures. Chapter IV is dedicated to an analysis of the gonads of replacement reproductives, which were collected in three different colonies of C. brevis. Colonies A and B were formed by a couple containing a neotenic and a primary reproductive. The primary king and the neotenic king showed ...

Reis de Isoptera fornecem grandes quantidades de espermatozoides viáveis à rainha. Contudo, o estudo do sistema reprodutor dos machos destes insetos tem sido negligenciado quando comparado ao das fêmeas. Com o objetivo de suprir essa lacuna, a presente pesquisa visou um estudo comparativo do sistema reprodutor em diferentes idades desses machos, incluindo ninfas e reprodutores alados. Desse modo, foram escolhidas três espécies, pertencentes a três famílias que ocupam posições evolutivas diferentes: Cryptotermes brevis, Coptotermes gestroi e Silvestritermes euamignathus. No Capítulo I, foi dado destaque à produção de espermatozoides e desenvolvimento das vesículas seminais em ninfas de último ínstar, reprodutores alados e reis com 6 meses e 1 ano de idade de C. brevis. Nas ninfas, os espermatozoides estão restritos aos testículos. O Capítulo II enfoca principalmente a histoquímica e ultraestrutura das vesículas seminais de C. gestroi e assinala o início da espermatogênese em ninfas de 3º ínstar, apesar de ninfas de 5º ínstar ainda não estocarem espermatozoides nas vesículas seminais. Nesta espécie, as vesículas seminais individualizadas apresentam uma região distal secretora e uma região proximal com função de armazenamento de espermatozoides. Adicionalmente, a histoquímica evidenciou polissacarídeos e proteínas na secreção presente na região distal destas estruturas. No Capítulo III, foi acompanhada a evolução do aparelho reprodutor em machos de S. euamignathus. Os resultados mostraram um amadurecimento precoce do sistema reprodutor dos machos e um aumento da produção de espermatozoides em reis de colônias maduras. Além disso, as vesículas seminais aumentaram muito nestes indivíduos e se apresentaram como porções especializadas dos dutos deferentes. Adicionalmente, dados morfológicos e histoquímicos permitem inferir que as vesículas seminais de reis funcionam mais como órgão de...
Keywords: Termites; Térmita; Aparelho genital; Morfologia